2021
DOI: 10.1021/acs.nanolett.1c01557
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Diamond—Diamane: Current State and Further Prospects

Abstract: Two-dimensional diamond, or diamane, is an ultrathin film with unique physical properties that combine the record values of the bulk crystal with the exciting features caused by the nanoscale nature. At the current stage of research, the diamane properties are mostly studied theoretically, and the main experimental efforts are directed at its synthesis. The latter is the trickiest problem since traditional methods involving the application of high pressure are not fully suitable due to the influence of surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 103 publications
1
87
0
Order By: Relevance
“…The uniqueness of these structures largely depends on the type of structural deformation, the amount of sp 3 carbon, the nature of hetero atoms, and the area of hydrogenated graphene. [56][57][58][59][60][61] Thus, the primary factor is to select proper functional groups in terms of their molecular or atomic states to form the desired structures in diamane. The selection of the fittest form of hydrogen in the crystal lattice of diamane is illustrated in Figure 3a.…”
Section: Structurementioning
confidence: 99%
See 4 more Smart Citations
“…The uniqueness of these structures largely depends on the type of structural deformation, the amount of sp 3 carbon, the nature of hetero atoms, and the area of hydrogenated graphene. [56][57][58][59][60][61] Thus, the primary factor is to select proper functional groups in terms of their molecular or atomic states to form the desired structures in diamane. The selection of the fittest form of hydrogen in the crystal lattice of diamane is illustrated in Figure 3a.…”
Section: Structurementioning
confidence: 99%
“…The selection of the fittest form of hydrogen in the crystal lattice of diamane is illustrated in Figure 3a. [61][62][63] In this regard, it is observed that uniform adsorption of atomic hydrogen to bilayer graphene leads to a strong chemical bonding between the layers of graphene, which, in turn, greatly stabilizes the structure of diamane, owing to the removal of Van der Waal forces. [64] Molecular hydrogen could only be used to perform physisorption on the surface of graphene rather than forming conventional bonds as discussed previously.…”
Section: Structurementioning
confidence: 99%
See 3 more Smart Citations